Pemulihan Ekonomi Pariwisata Bali di Era New Normal - Ni Made Rai Kristina (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Tourism is a very important sector in the income of the Indonesian economy in general and Bali in particular. Bali is a contributor to more than one third of the number of foreign tourists visiting Indonesia each year. Nature, customs and culture are the main factors that attract tourists to visit Bali. This greatly affects the economy of the Balinese people, because most of them are engaged in the tourism industry. The Covid-19 pandemic in all parts of the world, and also hit Indonesia, has an impact on the economic sector of Bali's tourism. The decline in Bali's tourism economy and the steps being taken to overcome the Covid-19 pandemic are very interesting to study. This study aims to explore the economic recovery of Bali's tourism in a new normal era. This research uses descriptive qualitative method. The results of this study indicate that it takes a long time to improve the tourism economy of Bali, so that recovery steps are needed. Starting July 9, the Provincial Government of Bali implemented the New Normal policy. This policy is implemented in collaboration with all components of Balinese society. Keywords : Tourism Economy, New Normal